2001
DOI: 10.1046/j.1355-557x.2001.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cysteinesulphinate decarboxylase activity in fish

Abstract: In order to elucidate the participation of L-cysteinesulphinate decarboxylase (CSD) in taurine synthesis in Japanese¯ounder, and the synthetic ability of taurine in other ®sh species, hepatic (or hepatopancreatic) CSD activities of several ®sh species were compared. Enzyme activity was determined by measuring the production of hypotaurine during an incubation of crude enzyme preparation with L-cysteinesulphinate as a substrate. HPLC was used for the analysis of hypotaurine. The enzyme activities of ®sh were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 13 publications
2
105
0
Order By: Relevance
“…Although animals inherently possess this metabolic pathway, kittens and human infants are not able to synthesize a sufficient amount of taurine from methionine due to low CSD activity and, thus, require taurine as a conditionally essential nutrient. In recent studies, CSD activity was measured in various fish species and found to be high in rainbow trout and tilapia and low in flounder, red sea bream, yellowtail, and bluefin tuna Thunnus orientalis [66,67]. It has also been demonstrated that flounder and red sea bream fed a cystine-supplemented diet do not have increased taurine content [68,69].…”
Section: Taurine Biosynthesismentioning
confidence: 99%
“…Although animals inherently possess this metabolic pathway, kittens and human infants are not able to synthesize a sufficient amount of taurine from methionine due to low CSD activity and, thus, require taurine as a conditionally essential nutrient. In recent studies, CSD activity was measured in various fish species and found to be high in rainbow trout and tilapia and low in flounder, red sea bream, yellowtail, and bluefin tuna Thunnus orientalis [66,67]. It has also been demonstrated that flounder and red sea bream fed a cystine-supplemented diet do not have increased taurine content [68,69].…”
Section: Taurine Biosynthesismentioning
confidence: 99%
“…In the present study, supplementation of cystine to the casine-based semi-purified diet did not promoted the growth of juvenile red sea bream, and the whole body taurine content did not increase at all. The activity of cysteinesulfinate decarboxylase, which is located in the trans-sulfuration pathway from cysteinesulfinate to hypotaurine, in red sea bream is only approximately half the levels of rainbow trout (Yokoyama et al, 2001). Therefore the red sea bream might have low capacity of taurine biosynthesis from cystine.…”
mentioning
confidence: 99%
“…Several studies have recently indicated that there are interspecific differences in the pathway and capacity of taurine biosynthesis in fish (Goto et al, 2001;Goto et al, 2003). The enzyme activity of cysteinesulfinate decarboxylase in red sea bream and Japanese flounder is only approximately half the levels of rainbow trout (Yokoyama et al, 2001), and thus this step is considered to be the rate limiting for taurine synthesis in the former species. In addition, taurine content in the muscle of rainbow trout (Yokoyama and Nakazoe, 1992) fed diets supplemented with taurine were remained at similar levels with each other irrespective of the dietary taurine contents.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of fish to synthesize taurine is species or developmental stage dependent Kim et al 2003Kim et al , 2005. The reason for such differences in their ability to synthesize taurine might be due to various activities of L-cysteine sulfinate decarboxylase, an enzyme required for the conversion from cysteine to taurine (De la Rosa and Stipanuk 1985;Takeuchi et al 2001;Yokoyama et al 2001). Although taurine is nonessential, its inclusion in diets is often recommended because of its auxiliary actions such as membrane protection, antioxidation and detoxification in mammals (Wright et al 1986).…”
Section: Introductionmentioning
confidence: 99%